Pediatric lung transplantation: 10 years of experience (Clinics, 2014)
Lung transplantation is a well-established treatment for advanced lung diseases. In children, the diseases that most commonly lead to the need for a transplantation are cystic fibrosis, pulmonary hypertension, and bronchiolitis. However, the number of pediatric lung transplantations being performed is low compared with the number of transplants performed in the adult age group. The objective of this study was to demonstrate our experience with pediatric lung transplants over a 10-year period in a program initially designed for adults.